Effects of culture conditions on proteolytic activity of Staphylococcus saprophyticus isolated from a traditional fermented condiment - Duanty, Putri Valentina; Pramono, Heru; Nirmala, Dwitha (Journal of Marine Resources and Coastal Management, 2026)
Madura petis is a traditional fermented condiment from East Java, Indonesia, made from shrimp or fish cooked with sugar to produce a rich, savory paste. Its characteristic umami flavour develops naturally during storage through spontaneous fermentation involving proteolytic microorganisms. The aims of the study were to analyze the production of protease in different culture condition and nutrition of Staphylococcus saprophyticus (strain PMB1-7) isolated from petis. The isolate was a Gram-positive, catalase-positive coccus that does not ferment mannitol and is resistant to novobiocin, a typical of S. saprophyticus. Growth profiling revealed it reached stationary phase after 12 h of culture. Protease activity assays were conducted under different media, pH levels, and incubation times to determine optimal enzymatic conditions. The highest proteolytic activity occurred in Nutrient Broth (proteolytic index: 1.09 ± 0.01), at neutral pH (1.22 ± 0.10), and after 24 hours of incubation (1.20 ± 0.00). These results offer valuable insights into the enzymatic behavior of S. saprophyticus during petis fermentation and provide a foundation for developing controlled fermentation approaches to enhance the flavour quality of traditional Indonesian condiments.